Grazing Behaviour of the Swamp Buffalo Bubalus bubalis - Kassim, H.; Baharin, K. (1979)
Studies on the grazing behaviour of the swamp buffaloes were carried out ill the Universiti Pertaniall Malaysia farm at Puchong. The results have shown that grazing took place throughout the whole 24-hour period with the greater part during the da;y. As a means of thermoregulation the animals wallowed in a pool of water during the day and night,. this was important in controlling body temperature and for the animals' well-being and hence their productivity. During the night the animals were either lying down or standing,.there was with very little walking. Rumination took place while the animals were wallowing or lying down.